Comparison of Outcomes of Colorectal Polypectomy Using Traditional Snare and Rotary Snare: A Prospective Randomized Controlled Trial - Lu Xu; Zhixing Zhang; Jiarong Xie; Lei Xu; Weihong Wang (Gastroenterology Research and Practice)
Background and Objective. The aim of the current study was to compare the efficacy and safety of polypectomy by using rotary snare vs. traditional snare during colonoscopy. Methods. A single-center randomized controlled trial, which included consecutive participants who were ≥18 years old and detected with polyp(s) during routine colonoscopy between July and September 2018, was conducted. Participants with colorectal polyps were randomized to receive polypectomy using rotary snares or traditional snares. The primary outcome measure was the comparison of the average time of removing a polyp between those two groups. The secondary outcome measure was to compare the polyp resection time by using SMSA (size, morphology, site, and access) scores. Results. A total of two hundred participants were included in this study. Of them, 100 participants were randomly assigned to the rotary snare group (214 polyps) and the other 100 participants were randomly assigned to the traditional group (232 polyps). The mean resection time was significantly shorter in the rotary snare group than in the traditional snare group (24.41±18.14 seconds vs. 29.53±25.74 seconds, P=0.021). In the subgroup analysis, the resection time was also shorter in the rotary snare group than in the traditional snare group in SMSA level 1 (18.51±8.26 seconds vs.23.84±15.07 seconds, P=0.013) and in SMSA level 2 (25.03±15.32 seconds vs.29.15±24.82 seconds, P=0.009), respectively. Conclusion. Colorectal polyps could be removed more efficient by using rotary snares than by using traditional snares in SMSA level 1 and SMSA level 2.